Groundwater quality assessment for different uses using various water quality ‘indices in Shamamik basin of Erbil-northern Iraq - Masoud Hussein Hamed (Zanco Journal of Pure and Applied Sciences, 2023)
The current study assessed the quality of groundwater in the Shamamik basin; the parameters were analyzed to determine ion distribution, classify groundwater, and identify the origin of groundwater in the study area.The EWQI of groundwater and hydrochemical parameters was based on 13 parameters including total hardness, electric conductivity,PH,TDS,Ca+2, Mg+2, Na+, K+, T.H, HCO3-, Cl-, NO3-, and SO4-2). The hydrochemical assessment demonstrated that the wells of the area studied contain more hydrochemical constituents. EC and TDS concentrations were found to be high in some wells in the studied area. According to the international standard guideline, it was concluded that the water samples collected from the wells are suitable for drinking purposes, agricultural activities as well as domestic use in the Shamamic basin of Erbil northern Iraq. The findings show that using ground water for irrigation will not harm plants because all water samples had excellent SAR for all samples, whereas RSC, with the exception of sample 1 from Tandora village, all samples are good to medium. All samples are excellent, according to PI, with the exception of sample 15 (Girdmala village), which is unsuitable for irrigation.Based on US salinity classification for irrigation 97% of the water samples presents medium quality for irrigation and can be used for these purposes without posing any danger to soil or crops.Origin of groundwater in studied are was Mg and Ca groups in both seasons and are the main contributors to the water type that Mg-Ca-HCO3 according to Pipper1944. Mg-Ca type for both seasons based on Durove classification of groundwater type origin.